Toward virtual design and optimization of a structural test monitored by a multi-view system. (February 2021) - Vitse, Matthieu; Poncelet, Martin; Iskef, Alaa Eddin; Dufour, John-Eric; Gras, Renaud; Bouterf, Amine; Raka, Bumedijien; Giry, Cédric; Gatuingt, Fabrice; Hild, Francois; Ragueneau, Frédéric; Roux, Stéphane
In order to characterize the mechanical behavior of a reinforced concrete beam–column joint, an experiment is designed whereby different histories of increasing cyclic loads are applied, and the structure deformation (as well as the morphology of apparent surface cracks) is studied using multi-view correlation. The complex three-dimensional geometry and the slender nature of the beam and column call for numerous digital cameras were positioned around the specimen. Assessing the feasibility of image acquisition and estimating a priori uncertainties on multi-view correlation became a true challenge. It is shown that the recourse to photo-realistic rendering software provides the needed tools to perform this experiment design optimization.